Corrupción: El cáncer que frena el desarrollo económico y social en el Perú. Una mirada desde el ejercicio del Derecho - Nakazaki-Servigón, César Augusto (2018)
On this occasion, ADVOCATUS had the opportunity to interview César Augusto Nakazaki Servigón, a lawyer with almost three decades of experience in litigation in the areas of criminal law and criminal procedure. He is also considered one of the most prominent lawyers in the country, for participating in complex cases within the Peruvian judicial system, such as the defense of three former presidents. In the following lines, the interviewee offered a brief analysis on the regulation of corruption in our country, as well as, the opinion of how judicial processes are being carried out in Peru.